Fabrication and dynamic compressive response of reaction sintering H-BN ceramic. (March 2020) - Gao, X J; Sun, M Y; Huang, W P; Zhang, M Y; Wu, Y Ch; Zhang, W; Wang, Ch
Abstract: Hexagonal boron nitride ceramic (h-BN) based on the nitridation of B powders was obtained by reaction sintering method. The dynamic compressive response was investigated using a Split Hopkinson pressure bar tester at high strain rates in a range of 0.8×10 3 −1.6×10 3 s −1 . By increasing the strain rate, the dynamic strength and the failure strain increased continuously. The compressive stress–strain curves exhibited universal three deformation regions, including inelastic deformation region, rapid loading region and failure region. The failure mode of the h-BN ceramic depended upon the strain rate.